Trash Trade and Environmental Regulations - Dawood, Shamila; Azhar, Ajra (Lentera Hukum, 2021)
Following China's decision to ban trash import in 2018, some countries in Southeast Asia are at the forefront of banning and imposing stringent measures to crackdown trash trade. The new trend in trash trade regulations had further impacted weaker countries and made a haven for dumping waste unless they adopt a uniform mechanism to regulate or completely ban trash trade within the region. This study aimed to analyze the recent response of some developing countries to the trash trade and how likely this response impact other countries in the same region, by taking into account the impact of the trash trade on the environment and health and waste handling capacity. This study adopted doctrinal analysis that combined descriptive and analytical approaches to analyze trash trade and regulation impacts in developing countries and arrived at a need for a holistic approach and national waste management policy to encourage the recycling industry in trash receiving states. This study found that although developing countries had a perfect set of rules and norms regarding sustainable waste management and protecting illicit trash trade, most of them had shortages due to internal and external factors. Solid waste management in developing and least developed countries was a never-ending problem due to the low technological requirements and economic investments. KEYWORDS: Trash Trade, Developing Countries, Environmental Justice.